PHYTOREMEDIATION PROPERTIES OF VEGETATION OF RECREATIONAL AREAS OF THE PARK-MONUMENT OF LANDSCAPE ART "DUBLIANSKYI" - Lysak Г.; Mazurak О.; Panas Н.; Salamakha І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Publications on the ability of autotrophic plants to purify atmospheric air, soils, natural water bodies, and artificially created lakes, ponds, and industrial wastewater lagoons were analyzed. The historical literary sources of the formation of park zones of the Dublianskyi Park-Monument of landscape art and the project documentation for the maintenance and reconstruction of the arboretum were studied. The current state of the park’s tree and shrub vegetation on the territory of Lviv National Environmental University and its phytoremediation properties were investigated. The plants-purifiers of the environment are grouped by systematic belonging to families and by their functional purpose. It has been established that Lemna minor L., Scirpus lacustris L., Typha angustifolia L., Stuckenia pectinata L., Sagittaria sagittifolia L., Iris pseudacorus L. carry out rhizophilisation in the reservoir in the park. They absorb water and pollutants with their rhizomes and roots, thus cleaning the saprophytic sediments of the lake basin. Phytoextraction of pollutants from the air is carried out by Tilia cordata Mill., Aesculus pavia L., Populus alba L., Salix fragilis L. And other representatives of tree and shrub vegetation, such as Thuja plicata D. Don., Pinus strobus L., Buxus sempervirens L., Taxus baccata L., Juniperus communis L., Abies alba Mill., perform phytovolatilisation – evaporating water and volatile elements through the spines and scaly leaves, enriching the environment with phytoncides. Symbionts that play a dual positive role – nourishing the soil with natural nitrogen fertilisers and simultaneously cleansing it of heavy metals – are representatives of the Fabaceae family: Cercidiphyllum japonicum Sieb. et Zucc.,Robinia pseudoacacia L., Catalpa bignonioides Walt., Caragana arbo-rescens Lam. Phyto-stimulation is provided by the development of bacteria of the Rhizobiaceae family.